The academisation of technical education at the end of the Ancien Régime La academización de la educación técnica afines del Antiguo Régimen - Agustín ESCOLANO BENITO (Historia de la Educación, 2013)
This study examines the genesis of academised technical education at the end of the Ancien Régime. The institutionalisation of the training of professionals of navigation, industry, commerce and agriculture emerged in the second half of the XVIII century in close relation to the programs of economic promotion, of diffusion of science and modern techniques and the pedagogical impulse of the Enlightenment. This process of academisation of the new knowledge would lead to the excision of the workshop- school and the revision of the teaching of the guilds, giving rise to a new model of education of the young, in contrast to the philological paradigm which had been predominant since the Renaissance in secondary schools. This new model was characterised by curricular planning according to the propositions of empirical science, mathematics and useful knowledge, by the discourse of the practicality of knowledge and by the new ethos of the middle class. Este trabajo examina la génesis de la educación técnica academizada a finales del Antiguo Régimen. La institucionalización de la formación de los profesionales de la navegación, la industria, el comercio y la agricultura emerge en la segunda mitad del siglo XVIII en estrecha relación con los programas de fomento económico, de difusión de la ciencia y de la técnica modernas y del impulso pedagógico de la Ilustración. Este proceso de academización de los nuevos saberes desencadena la escisión escuela-taller y la revisión de la enseñanza gremial, dando origen a un nuevo modelo de educación de la juventud, contrapuesto al paradigma filológico dominante desde el Renacimiento en las escuelas secundarias y caracterizado por una ordenación curricular conformada a los presupuestos de la ciencia empírica, la matemática y los conocimientos útiles, por el discurso de la practicidad del saber y por el nuevo ethos de la burguesía.